Enhanced Teleoperation of Robotic Arms Through Master-Slave Configuration With Multithreading - Zainudin, Ahmad Faiz Fawzan Ahmad; Zaman, Mohd Hairi Mohd; Ibrahim, Mohd Faisal; Zulkifley, Mohd Asyraf; Marzuki Mustafa, M. (IEEE access, 2025)
Teleoperation systems are crucial in various industrial applications, including medical surgeries and the operation of remotely controlled robots. However, latency issues significantly impact precision and responsiveness, presenting a critical problem that requires extensive attention. Moreover, the dissimilarities in design, functionality, and control mechanisms between the master device and the slave robot arm introduce additional layers of complexity, making the operation and synchronization of the system more challenging. This paper aims to address these gaps by pursuing two primary objectives: to design and fabricate a structurally similar master device that replicates the joint configuration and range of motion of the Universal Robot's UR10e robot arm, and to implement control strategies that minimize latency and improve stability. The master device was implemented using a modified Hiwonder Synchronization Controller configured to replicate the UR10e's kinematic structure. It was integrated with six connected potentiometers in series and evaluated along with the UR10e robotic arm in a lab-scale setup, with all components connected via ROS Noetic. The system was tested in point-to-point motion tasks and a newly added obstacle-constrained task to assess latency, stability, and robustness to sensor noise. Low-pass filtering techniques were applied to suppress signal noise and improve trajectory smoothness, while multithreading methods were used to separate sensor polling and data transmission processes. Experimental results showed that latency was reduced by 91%, from an average of 119.0 ms to 10.2 ms in all tasks. The total system latency decreased by over 85%, from 228.0 ms to as low as 32.0 ms. For stability, the peak overshoot on the Y-axis was reduced by 98% from 104.0°to 2.3°, and the steady-state error on all axes was minimized, with overall improvements exceeding 95%. A preliminary user study showed that task completion times significantly improved after training, demonstrating the system's intuitive design and low learning curve. These outcomes were visualized using error bar latency plots and histogram latency distribution, confirming improved system responsiveness, reduced jitter, and the elimination of catastrophic delays. This work presents a low-cost, scalable solution for improving the fidelity and responsiveness of master-slave teleoperation, with potential applications in industrial automation, agriculture, and remote manipulation in hazardous environments. Future work will focus on wireless communication, haptic feedback integration, and expanded validation under real-world agricultural conditions.